Rabbit researches at the Instituto de Ciencia Animal - Valdivié, Manuel; Ponce de León, Raquel (Cuban Journal of Agricultural Science, 2016)
an emphasis on genetic improvement, use of food produced in Cuba, Physiology and the study of rabbit gastrointestinal tract. For more than 40 years, ICA has been an adviser in studies of genetic improvement in Cuba, and has recommended the use of different forages containing between 14 and 32 % of crude protein, as well as some other food of national production, which are used by an important amount of medium and small producers of rabbits, with positive results. The institute also selected a system of equations for estimating digestible energy of food destined to rabbits. ICA also designed a program that formulates rations destined to rabbits, with all types of food. During this period, the institute participated on the training of rabbit producers and the graduation of six PhD students of Veterinary Sciences and seven Masters in Science. During this period, a manual on rabbit rearing and a book about their feeding were written.Key words: rabbits, feeding, management